Sex as a Potential Moderator for Baclofen Response in the Treatment of Alcohol Dependence - Morley, Kirsten C.; Louie, Eva; Hurzeler, Tristan; Baillie, Andrew; Dore, Glenys; Phung, Nghi; Haber, Paul S. (Frontiers in Global Women's Health, 2022)
Background and Aims: Recent studies indicate that sex may moderate response to baclofen in the treatment of alcohol use disorder. We conducted a secondary analysis of the BacALD trial (1) to examine the role of sex in the response to baclofen in reducing alcohol consumption. Methods: Alcohol dependent patients (N = 74 males, 30 females) treated for 12 weeks with baclofen (30 mg/day or 75 mg) or placebo. Predefined primary outcomes included time to lapse (any drinking) and relapse (> 5 drinks/day in men and > 4 in women). Other outcomes included drinks per drinking day, number of heavy drinking days, percentage days abstinent. We also examined frequency of adverse events with an exploratory dose response analysis. Results: There was a main effect of baclofen for days to first lapse for females (Log Rank: 2= 6.23, P = 0.01, d = 0.49) but not males (Log Rank: 2= 2.48, P =0.12, d = 0.22) and a marginal effect of baclofen for days to first relapse for females (Log Rank: 2= 3.15, P =0.08, d = 0.27) but not males (Log Rank: 2= 2.03, P =0.16, d = 0.17). There were no significant effects of sex on the frequency of adverse events reported for the combined or between dose analysis (P’s > 0.44). Conclusion: Baclofen significantly delayed the time to lapse for females but not males. These findings provide some support for the hypothesis that sex may be a potential moderator of baclofen response in the treatment of alcohol use disorder.